Modeling of Sandy Soil Compaction and Water Holding Capacity Due to Biogas Slurry Ameliorant - Yudhistira, D. T; Ngadisih, Ngadisih; Karyadi, Joko Nugroho Karyadi; Tirtalistyani, Rose; Ismail, M. H.; Mawandha, Hanggar Ganara (IOP Publishing Ltd, 2022)
Model could be used to study the behavior of real systems such as hydrosphere (soil system) for improving their performance as basis of decision-making that promote the sustainability. Here, the study focused on SDGs point 15, how the agriculture particularly soil management should keep the life on land. Biogas slurry (BS) is a liquid-solid mix waste from livestock that useful for soil improving soil quality. Sandy soil has some limitations when used as media of plant cultivation, mainly poor in water holding capacity and less of organic content. This study aimed to measure and explore the sandy soil quality (soil compaction, SC and water holding capacity, WHC) due to BS application. A completely randomized design (CRD) in laboratory was adopted in this study where soil and BS put in a pot of diameter and height of 8.2 cm and 12 cm, respectively. The experiment was carried out with treatment of sandy soil as control (K), sandy soil and BS dose15 ton/ha (D1), 30 ton/ha (D2), and 45 ton/ha (D3). The soil was incubated 84 days that every 14 days (incubation time, IT) the SC and WHC were measured. Mathematical model and Two Ways ANOVA Test were applied to analyze the data. Logistic equation was acceptable (R2 > 80) to describe soil compaction behavior in sandy soil with BS ameliorant. The SC rate of K, D1, D2, and D3 treatments were-0.0251,-0.0524,-0.0280, and-0.0360, respectively. This study revealed BS and IT significantly affect SC and WHC of sandy soil with BS ameliorant.